Molecular Approaches in Arbuscular Mycorrhizal Research: A Review - R. R. Pandey2, D. Sharmah1, D.K. Jha1 and (Journal of Phytology, 2010)
Arbuscular mycorrhizal fungi (AMF), belonging to phylum Glomeromycota, are among one of the key species groups that inter-connect plants into a functional web. Most of the research work on AMF is focused mainly on taxonomy, phylogeny, ecology, genetics and functional symbiosis with some major insights gained in biology of the fungi in the last decade, with application of molecular methods and revolutionary technological advancement. In this article, we reviewed the current scenario of molecular investigations on AMF all over the world, and compare it with conventional techniques to bring about the pros and cons. Since no technique is a panacea, we advocate the use of both molecular and microscopy methods to characterize AMF communities in plant roots and to construct a robust phylogenetic tree. Key words: Arbuscular mycorrhiza, Molecular methods, Primer, rDNA <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">D. Sharmah et al. Molecular Approaches in Arbuscular Mycorrhizal Research: A Review. J Phytol 2/7 (2010) 75-90.